2005
DOI: 10.1196/annals.1342.034
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Effect of β‐N‐Methylamino‐L‐Alanine on Retzius Nerve Cells of the Leech Haemopis sanguisuga

Abstract: We investigated the effect of beta-N-methylamino-L-alanine (L-BMAA) on input membrane resistance of leech Retzius nerve cells and the effect of the same substance on the membrane potential in the presence of 20 mM bicarbonate. Results of our experiments show that L-BMAA significantly reduces input membrane resistance on our model. This leads to the conclusion that L-BMAA depolarizes the cell by increasing membrane permeability and conductance. The effect of L-BMAA in 20 mM bicarbonate is significantly higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…36 Nedeljkov et al investigated the effects of L-BMAA on Retzius nerve cells of isolated ganglia of the leech Haemopis sanguisuga and showed that the presence of bicarbonate ions produces a 4-fold increase in BMAA-induced depolarization of the membrane potential. 37 Lopicic and colleagues, using the same model, reported that application of both 1 mmol L -1 L-BMAA in Ringer solution containing 20 mmol L -1 bicarbonate caused a significant 74 % decrease in the input resistance of directly polarized membrane and that the non-NMDA receptor antagonist 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) at a concentration of 100 μmol L -1 decreased the effect of L-BMAA on membrane potential by 57 %. The authors also presented evidence for a rise in the intracellular Na + concentration (Na + ) c and decrease in the intracellular K + concentration (K + ) c during BMAA induced depolarizations.…”
Section: Mechanisms Of Bmaa Neurotoxicitymentioning
confidence: 97%
“…36 Nedeljkov et al investigated the effects of L-BMAA on Retzius nerve cells of isolated ganglia of the leech Haemopis sanguisuga and showed that the presence of bicarbonate ions produces a 4-fold increase in BMAA-induced depolarization of the membrane potential. 37 Lopicic and colleagues, using the same model, reported that application of both 1 mmol L -1 L-BMAA in Ringer solution containing 20 mmol L -1 bicarbonate caused a significant 74 % decrease in the input resistance of directly polarized membrane and that the non-NMDA receptor antagonist 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) at a concentration of 100 μmol L -1 decreased the effect of L-BMAA on membrane potential by 57 %. The authors also presented evidence for a rise in the intracellular Na + concentration (Na + ) c and decrease in the intracellular K + concentration (K + ) c during BMAA induced depolarizations.…”
Section: Mechanisms Of Bmaa Neurotoxicitymentioning
confidence: 97%
“…[73] measured the membrane input resistance of the nerve cells of the leech Haemopis sanguisuga after treatment with BMAA (100 μM–10 mM) and HCO 3 − (20 mM). A significant reduction in input membrane resistance was measured, indicating that BMAA depolarizes the cell by increasing membrane permeability and conductance.…”
Section: Summary Of the Multiple Mechanisms Of Bmaa Activitymentioning
confidence: 99%
“…The physiological concentrations of bicarbonate ions (10 mM and above) reacts with BMAA to form a β-carbamate [60]. In this form, BMAA can compete in binding various glutamate receptors, such as NMDA receptors [55,56,64,65], AMPA receptors [55,56], and metabotropic and ionotropic glutamate receptors [65,73,81,84] (Figure 3i). Activation of the various glutamate receptors leads to shifts in cellular ion concentrations resulting in increases in Na + [81] and Ca 2+ [70,76,84], and a decrease in K + [81] concentrations (Figure 3ii).…”
Section: A Summary Of the Mode Of Action Of Bmaa Based On The Currmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive in vitro experiments have demonstrated that the neurotoxicity of BMAA for neurons is a result of multiple mechanisms including action at NMDA ( N -methyl- d -aspartic acid) or AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid)/kainate receptors, generation of ROS (reactive oxygen species), and production of excessive dopamine [3,4,5,6,7]. Recent reports have documented that BMAA inhibited antioxidant enzymes of the macrophyte Ceratophyllum demersum and of aquatic plants ( Lomariopsis lineata , Fontinalis antipyretica , Riccia fluitans , and Taxiphyllum barbieri ), indirectly implicating the induction of oxidative stress in plants by BMAA [8,9].…”
Section: Introductionmentioning
confidence: 99%